(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study assessed the soil nutrient status of Nauclea diderrichii and Terminalia superba plantations in the Forestry Research Institute of Nigeria, Oyo State, Nigeria, to address the limited knowledge on soil nutrients in monoculture plantations in the region. Soil samples were systematically collected from five points at 50m intervals at two depths (0-15 cm and 15-30 cm). The samples were analysed for particle size distribution, Water Holding Capacity (WHC), pH, nitrogen (TN), Available Phosphorus (AP), Organic Carbon (OC), exchangeable cations (Ca²⁺, Mg²⁺, K⁺, Na⁺), cation exchange capacity (CEC), and micronutrients (Fe³⁺, Cu²⁺, Mn²⁺, Zn²⁺). Nauclea diderrichii exhibited slightly lower pH (6.3) and higher WHC (76.52%) compared to Terminalia superba (pH 6.8, WHC 62.25%). The mean OC, TN, and AP were higher in Terminalia superba (35.25 4.79; 2.95) compared to Nauclea diderrichii (25.24; 2.21; 3.32). The study found a strong correlation between the soil chemical (r = 0.962; p < 0.01) and physical properties (r = 0.989; p < 0.01) under Nauclea diderrichii and Terminalia superba, indicating that both species influence soil nutrient status and structure. For exchangeable cations and CEC, Nauclea diderrichii showed higher values, with Ca²⁺, Mg²⁺, K⁺, Na⁺, and CEC at 3.58; 1.56; 0.51; and 6.3, respectively, compared to Terminalia superba. These findings indicate that Nauclea diderrichii plantations have higher soil nutrient accumulation, suggesting better soil fertility. The study recommends that this species be prioritized in afforestation and reforestation programs in Nigeria to enhance soil fertility and support sustainable forest management.